Electrochemical Advanced Treatment of Organics from Coking Wastewater Using Three-Dimensional Electrodes - Wang, Hao; Chen, Jianwei; Li, Xuejin (Asian Journal of Chemistry, 2013)
Saturated coke, as filler materials, was applied to advanced treat coking wastewater by three-dimensional fixed bed electrode reactor. It was indicated that coke powder could be used as catalytic electrode, and optimized conditions were of electrolysis time 1 h, current density 8A, particle size 10-20 mesh number, dosing quantity 400 mL, plate spacing 1 cm, pH 3, the removal efficiency of COD was up to 70 %. Meanwhile, the degradation mechanism of COD in the experiment was also carried out and obeyed the first order dynamics.